Optimization of a multiobjective programming problem - Lim, Kong Teong (Universiti Utara Malaysia, 1999)
The purpose of this paper is to suggest the use of the Generalized Distance Approach in the field of multiobjective programming to find "compromising" conditions on the decision variables that will give a "near" optimal value for each of the objectives. A global optimization technique called the Controlled Random Search (CRS)procedure has been used to minimize the distance function derived from the Generalized Distance Approach. It is numerically shown that this approach works well in solving multiobjective optimization problems.